The Role of Diagnostic Ability in Markets for Expert Services - Fang Liu; Alexander Rasch; Marco Alexander Schwarz; Christian Waibel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
In credence goods markets, experts have better information about the appropriate quality of treatment than their customers. Experts may exploit their informational advantage by defrauding customers. Market institutions have been shown theoretically to be effective in mitigating fraudulent expert behavior. We analyze whether this positive result carries over to a situation in which experts are heterogeneous in their diagnostic abilities. We find that efficient market outcomes are always possible. However, inefficient equilibria can also exist. If, in equilibrium, experts provide diagnosis-independent treatments, an increase in experts' ability or in the probability of high-ability experts might not improve relative market efficiency.
Keywords: D82; L15; 330; credence good; diagnosis; expert; fraud; overtreatment; undertreatment